THE EFFECT OF MAT PILATES IN LUMBAR FLEXIBILITY OF OVERWEIGHT AND OBESE CHILDREN - Graciela Eunike Hartono; Tanti Ajoe Koesoema; Rahmi Isma AP; Dimas Tri Anantyo (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background : Overweight and obesity are the conditions where lumbar have to bear more load, and it will decrease its flexibility. Decrease of lumbar flexibility will affect the range of motion. Based on some literatures, mat pilates will increase the ability on lumbar flexibility, however there is no evidence effect of mat pilates in children, especially overweight and obese children. Aim : To know the effect of mat pilates on lumbar flexibility of overweight and obese children. Method :This study was pre experimental one group pre and post test design with 20 subjects based on inclusion dan exclusion criteria. Subjects did mat Pilates exercise for 12 times. Lumbar flexibility was measured by Modified Modified Schober Test for lumbal flexion and extension before intervention and after 4 weeks mat pilates exercise. Data analyzed by SPSS using Saphiro Wilk test as data’s nomalities test and Paired T test as hypothesis test. Result : The mean of MMST Flexion pre and post test after Mat Pilates have increased from 3,15±0,3118 cm to 7,63±0,4 cm. The mean of MMST extension pre and post test after Mat Pilates hav e increased from 1,415±0,21 cm to 3±0,236 cm. The means of a BMI Post test (24,89 ± 0,9 kg/m2) is higher than the mean of a BMI Pre test (24,86 ± 0,8 kg/m2).The significant result proves the effect of mat pilates in lumbar flexibility of overweight and obese children which measured by MMST Flexion and MMST Extension. The result of p value for MMST Flexion is p=0,00 and the result of p value for MMST Extension is p=0,00 which both of MMST flexion and Extension are significant or different. Conclusion : Mat pilates can increase the lumbar flexibility of overweight and obese children.Keyword: Mat Pilates, Lumbar Flexibility, overweight and obese children.